Mediation and law: A practical presentation of mediation and its legal foundations (Mediation und Recht: Eine praxisnahe Darstellung der Mediation und ihrer rechtlichen Grundlagen) - ADE, Juliane (Institutional Knowledge at Singapore Management University, 2017)
Here is the abstract for this publication: This book offers an in-depth examination of the practice of mediation within the German legal system. Unlike other books which treat mediation theory, practice and law as very distinct areas for investigation and commentary, this work weaves together these different perspectives. Its unique contribution is the way in which it convincingly highlights how mediators, regardless of whether or not they have a legal background, need familiarity not only with the legal framework within which mediation operates – ‘the law of mediation’ – but also with the dynamics of ‘law in mediation’. While the focus is on mediation in Germany, comparative insights lend an international legitimacy and gravitas to the arguments and views presented. The authors, Juliane Ade and Nadja Alexander, bring their vast combined interdisciplinary experience of mediation in Germany and internationally to this book.